Do randomized clinical trial selection criteria reflect levels of risk as observed in a general population of acute myocardial infarction survivors? The PEGASUS trial in the light of the FAST-MI 2005 registry. (15th November 2016) - Puymirat, Etienne; Schiele, François; Zeller, Marianne; Jacquemin, Laurent; Leclercq, Florence; Marcaggi, Xavier; Ferrières, Jean; Simon, Tabassome; Danchin, Nicolas; ,
Abstract: Background: Few clinical trials have focused on populations with a history of distant myocardial infarction (MI). The PEGASUS trial assessed the impact of dual antiplatelet therapy in such patients, selected by enrichment criteria of high cardiovascular risk. Whether the PEGASUS population reflects the risk of a broader post-MI population is questionable. We analyzed whether 4-year mortality of a routine-practice population would differ according to the inclusion and exclusion criteria used in PEGASUS. Methods: FAST-MI is a nationwide French registry recruiting acute MI patients in November 2005; 2490 patients alive and without recurrent MI at one year were classified into three groups: Group 1 ("PEGASUS-like" population; n = 1395; 56%), Group 2 (population having ≥ 1 exclusion criterion for the trial; n = 677; 27%), and group 3 (population meeting neither the PEGASUS inclusion nor exclusion criteria; n = 418, 17%). Results: Group 1 patients were older than Group 3 patients, with higher GRACE scores, more comorbidity, and less STEMI, but were younger than the PEGASUS trial population. Enrichment criteria successfully defined a population at higher risk: 4-year survival 83% in Group 1, 97% in Group 2, and 68% in Group 3 (P < 0.001). Among risk-enrichment criteria, age alone was highly discriminant: in PEGASUS-like patients, survival was 78% in those ≥ 65 versus 94% in those < 65 years. Conclusions: Enrichment criteria used in PEGAGUS succeed in defining a population at increased risk in patients with prior MI, age being the most discriminant factor. The trial population, however, was notably younger and more masculine than the corresponding real-life population in France. Clinicaltrials.gov number: NCT00673036 . Highlights: We investigated the PEGASUS-TIMI 54 trial criteria in a real life post-MI population. Patients were categorized according to criteria used in PEGASUS trial. We used data from a nationwide French registry including 3670 patients (FAST-MI). Enrichment criteria used in PEGAGUS succeed in defining a high-risk population. Age represents the most discriminant factor.